Joseph Conrad and Terrorism Today - Wexler, Joyce. author. aut Link
IX, 121 p. 1 illus.
Keywords: “Drawing extensively on contemporary research in Terrorism Studies, Joyce Wexler sheds new light on Conrad’s understanding of the complications and contradictions of this controversial topic. She convincingly demonstrates that many of the disputes about how to read his works reflect disagreements about terrorism—and that more often than not Conrad was right, and his critics wrong. Teachers and students will find this a useful book for many reasons—for the information it provides about Terrorism Studies, for the perspectives it offers on Conrad’s relevance for issues of contemporary concern, for Wexler’s thorough, up-to-date accounts of the Conrad criticism, and for her sensible, detailed readings of often-taught texts.” --Paul Armstrong, Professor of English, Brown University, USA This book explores how the anarchist fiction of Joseph Conrad can help us understand terrorism today. Conrad undermines the popular view that terrorists are fanatics. He portrays anarchists and police as counterparts driven by the human desires for autonomy and affiliation, the need to control their own lives and to be part of a group. Postcritique encourages readers to consider the accuracy of such information, and research in Terrorism Studies confirms Conrad’s insights: his characters are more realistic and his political stance is more hopeful than critics have recognized. Joyce Wexler is Professor Emerita of English at Loyola University Chicago, USA. She is President of the Joseph Conrad Society of America. Her publications include Joseph Conrad and Postcritique (co-edited with Jay Parker), Violence Without God, Who Paid for Modernism, and Laura Riding’s Pursuit of Truth.